Effects of perceived indoor temperature on daylight glare perception. Issue 8 (16th November 2016) - Garretón, Julieta Yamin; Rodriguez, Roberto; Pattini, Andrea
Abstract : This research investigates the effects of perceived indoor temperature on glare sensation. A laboratory experiment was carried out where volunteers ( n  = 19) performed an office-like computer task. Three scenarios with sunspots over the desk were evaluated: a cold scenario, a comfort scenario and a hot scenario. All had the same vertical illuminance at the eye and luminance ratios. Discomfort glare was measured with the predictive daylight glare probability (DGP) model; actual perception of glare was assessed with glare sensation vote (GSV) scale; while thermal comfort was evaluated with thermal sensation vote (TSV) scale. In order to know how much the perceived temperature contributes to the model, an ordinal regression was performed. The result showed a Nagelkerke pseudo- R 2  = 0.52, p = 0.001, indicating that the perceived temperature affected glare predictions. This is an improvement in the understanding of daylight glare, which will allow researchers and practitioners to make informed decisions about sustainable design and occupant comfort. In conclusion, a more comprehensive glare model should include perceived temperature as a variable of the current glare model. Also, the results suggest that DGP should be used only when the person is in thermal comfort.